Estimación de parámetros cinéticos para el consumo de sustrato de piña (Ananas Comosus Merr.) Por lactobacillus acidophilus en la producción de ácido láctico (2018)
This project is part of a larger study in which the kinetics of biomass growth and kinetics for the production of lactic acid are described. However, these are independent projects and it should be noted that the elaboration of the fermentation and taking of all the experimental data for the adjustment of the models was a joint work with colleagues that describe the growth of the biomass and the production of the primary metabolite , this project does not intend to create a new kinetic model by means of experimental data since it is complex to do it and of long time of execution for this reason the experimental data obtained in models present in bibliography will be evaluated. The pineapple waste has a large amount of sugars, which can be used by microorganisms that are able to degrade them and generate metabolites or ferme bntation products.